PELAKSANAAN KEWENANGAN DINAS PEMBERDAYAAN PEREMPUAN, PERLINDUNGAN ANAK, PENGENDALIAN PENDUDUK DAN KELUARGA BERENCANA DALAM PENGENDALIAN KUANTITAS PENDUDUK DI KABUPATENPELALAWAN TAHUN 2018 - Ari Utama Putra; Wazni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The background of the writing of this thesis is based on the researcher’s view of the phenomenan that occurs in population control, including mandatory governmental affairs tha are not related to basic service and enter into concurrent government affairs in controlling the population quantity in pelalawan regency in 2018.Researchers used a qualitative approach. This type of research is descriptive. Research location in the office of women’s empowerment, child protection, population control and family planning (DP3AP2KB) Pelalawan regency. With the type and source of research data is divided into primary data in the form of purposive informant retrieval techniques and secondary data in the form of supporting data related to population growth.  Data collection technique ised interviews and documentation, while data analysis was carried out using quantative analysis.Based on the result of research and discussion, it is know that in controlling the population quantity in pelalawan regency in 2018. It has been going well, this is indicated by the emergence of several strategies in controlling population quantity in pelalawan regency in 2018, namely by implementing several population programs. For example the kampung KB program as the main program. Meanwhile, the obstacle to pelalawan regency is the devision distict so that it attracts the attention of the outside community to stay in pelalawan regency because whatever is categorized as the result of expansion, there will be rapid development and growth. The emergence of company is one the perfect of the expansion area which is also on attraction for coming to pelalawan regency because a new company in a area will require a large number of workers.  Keywords :      Authority Implementation, Women Empowerment Service, Child Protection Population Control And Family Planning, Population Quantity Control